2021
DOI: 10.1002/aenm.202100303
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Modified Atomic Sites Within a Multicomponent Co/Cu Composite for Efficient Oxygen Electroreduction

Abstract: Moreover, the stability issues of Pt-based catalysts (e.g., the crystallite dissolution and nanoparticle agglomeration) have also jeopardized the reliability of power systems including ORR as a half reaction. [7,8] In these regards, there is a general call for the replacement of the Pt-based composites with cost-effective, durable and highly active ORR catalysts.During the past few years, nitrogencoordinated transition metal species (TM-N x ) that are embedded within a carbon matrix have emerged as a class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 58 publications
1
59
0
Order By: Relevance
“…A manual grinding-pyrolysis solid-phase synthesis method is used to prepare Cu-layer-decorated Co nanoparticles which are confined in a Cu-N x and Co-N x codoped graphene nanoshell (Figure 3A). [118] For this specific example, a stoichiometric ratio of metal precursors (Co(NO 3 ) 2 •6H 2 O and Cu(NO 3 ) 2 •3H 2 O)…”
Section: Solid-phase Synthesismentioning
confidence: 99%
“…A manual grinding-pyrolysis solid-phase synthesis method is used to prepare Cu-layer-decorated Co nanoparticles which are confined in a Cu-N x and Co-N x codoped graphene nanoshell (Figure 3A). [118] For this specific example, a stoichiometric ratio of metal precursors (Co(NO 3 ) 2 •6H 2 O and Cu(NO 3 ) 2 •3H 2 O)…”
Section: Solid-phase Synthesismentioning
confidence: 99%
“…[8] Zhang et al reported an atomically dispersed Co and Cu dual metaldoped carbon material with Cu-decorated Co NPs encapsulated inside, exhibiting a remarkable ORR catalytic performance. [9] The co-existed NPs and TM-N x species significantly regulated the electronic structure of Co-N x active sites, which optimized…”
mentioning
confidence: 99%
“…The significant geometrical, electronic, and synergistic effects between the different components in the alloys contribute to the enhancement of the intrinsic catalytic activity relative to that of single metal counterparts. 46 In addition to CoNi particles, some “alloy-free” area can be distinguished by the emergence of Co signals but lack of Ni signals, which indicates the presence of Co–N x –C sites. In Fig.…”
Section: Resultsmentioning
confidence: 99%